Four new species of the genus Ischnothyreus from Hainan Island, China (Araneae, Oonopidae) - Tong, Yanfeng; Li, Shuqiang (Zootaxa, 2012)
Four new species of the genus Ischnothyreus are reported from Hainan Island, China: I. auritus sp. nov., I. spineus sp. nov., I. xui sp. nov. and I. yuanyeae sp. nov.